Analisis Pengaruh Kualitas Manajer dan Kompensasi terhadap Retensi Karyawan pada PT Idola Insani Garmen - Dwi Irvianti, Laksmi Sito; Gunawan, Wendy; Kho, Jhony (Binus Business Review, 2011)
PT Idola Insani Garment is generally moved in garment industry, especially clothing. The method in this research is to analyze the effects of manager quality and its compensation towards employee retention in the company. The analysis method in this research is regretion analysis. The data is gathered from questionnaire and interview of 64 current employees in the company. The questionnaire is using Likert scale that used to identify employeeâs disagreement and agreement rate towards statements in the questionnaire. The result in this research is to acknowledge that manager quality variable has a weak relationship and concurent towards employees retention, that is 0,355, meanwhile compensation variable has a strong and concurent relationship towards employees retention, that is 0,586. That concludes that the compensation variable has more effects on employees retention than manager quality.Â